Dukungan sosial dan kepercayaan diri orang tua yang memiliki anak berkebutuhan khusus - Al Alufi, Faizatun Nissa; Saifullah, Saifullah (PSYCOMEDIA : Jurnal Psikologi, 2023)
This research uses correlational quantitative method. Participants in this study amounted to 40 people consisting of fathers and mothers of parents of children with special needs. The data analysis of this research used mediation analysis with the help of the Statistical Program for Windows (SPSS). The results of this study indicate that social support has a positive and significant relationship with self-confidence in children's parents. The suggestion in this study is that the results of this study can be used as a basis for developing social support in the community for parents who have children with special needs and for further researchers to be able to examine other psychological resources as an effort to increase self-confidence in parents who have children with special needs. special.